Transformation of Islamic Education (PAI) Learning through Project-Based Learning in the Context of Deep Learning at SMA Negeri 1 Kediri - Mohammad Nabil; Karisma Dewi Puspasari; Fina Miftahul Fa’izatil Ulya; Iqbal Ghofur Pratama; Ahmad Dani Aufina (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Islamic Religious Education is understood as a systematically and pragmatically designed effort to guide students in living their lives in accordance with Islamic teachings. Observations conducted at SMA Negeri 1 Kediri indicate that Islamic Religious Education teachers have begun implementing innovative learning strategies aligned with the principles of the Merdeka Curriculum by utilizing a deep learning approach. Deep learning is a pedagogical model aimed at enhancing students’ understanding through comprehensive exploration and critical engagement by integrating mindful learning, meaningful learning, and joyful learning. This approach enables students to develop both intellectual and emotional intelligence simultaneously. In its implementation, the learning process employs the Project-Based Learning (PjBL) model, which provides students with opportunities to actively participate in producing a project as part of their learning process. Project-Based Learning has the potential to strengthen the “meaningful” aspect of learning through the creation of tangible works directly related to Islamic values. Through this process, students not only understand concepts cognitively but also internalize the spiritual and social meanings embedded within them. The project-based approach provides space for students to express themselves creatively and joyfully, making learning more engaging and relevant to their daily lives. The resulting works can be analyzed, reflected upon, and used as concrete examples of the conscious application of Islamic values in everyday life.